High‐Performance Sodium‐Ion Hybrid Supercapacitor Based on Nb2O5@Carbon Core–Shell Nanoparticles and Reduced Graphene Oxide Nanocomposites. (31st March 2016) - Lim, Eunho; Jo, Changshin; Kim, Min Su; Kim, Mok‐Hwa; Chun, Jinyoung; Kim, Haegyeom; Park, Jongnam; Roh, Kwang Chul; Kang, Kisuk; Yoon, Songhun; Lee, Jinwoo
Abstract : Sodium‐ion hybrid supercapacitors (Na‐HSCs) have potential for mid‐ to large‐scale energy storage applications because of their high energy/power densities, long cycle life, and the low cost of sodium. However, one of the obstacles to developing Na‐HSCs is the imbalance of kinetics from different charge storage mechanisms between the sluggish faradaic anode and the rapid non‐faradaic capacitive cathode. Thus, to develop high‐power Na‐HSC anode materials, this paper presents the facile synthesis of nanocomposites comprising Nb2 O5 @Carbon core–shell nanoparticles (Nb2 O5 @C NPs) and reduced graphene oxide (rGO), and an analysis of their electrochemical performance with respect to various weight ratios of Nb2 O5 @C NPs to rGO (e.g., Nb2 O5 @C, Nb2 O5 @C/rGO‐70, ‐50, and ‐30). In a Na half‐cell configuration, the Nb2 O5 @C/rGO‐50 shows highly reversible capacity of ≈285 mA h g −1 at 0.025 A g −1 in the potential range of 0.01–3.0 V (vs Na/Na + ). In addition, the Na‐HSC using the Nb2 O5 @C/rGO‐50 anode and activated carbon (MSP‐20) cathode delivers high energy/power densities (≈76 W h kg −1 and ≈20 800 W kg −1 ) with a stable cycle life in the potential range of 1.0–4.3 V. The energy and power densities of the Na‐HSC developed in this study are higher than those of similar Li‐ and Na‐HSCs previously reported. Abstract : Nb2 O5 @Carbon core–shell nanoparticles and reduced graphene oxide nanocomposites (Nb2 O5 @C/rGO) for new energy storage systems, namely sodium‐ion hybrid supercapacitors (Na‐HSCs), are presented. A Na‐HSC system comprising an Nb2 O5 @C/rGO anode and an MSP‐20 cathode delivers high energy and power densities (≈76 W h kg −1 and ≈20 800 W kg −1 ), with excellent cycling stability.